2007
DOI: 10.1103/physrevb.76.134518
|View full text |Cite
|
Sign up to set email alerts
|

Hole-doping dependence of the magnetic penetration depth and vortex core size inYBa2Cu3Oy: Evidence for stripe correlations near

Abstract: We report on muon spin rotation (µSR) measurements of the internal magnetic field distribution n(B) in the vortex solid phase of YBa2Cu3Oy (YBCO) single crystals, from which we have simultaneously determined the hole doping dependences of the in-plane Ginzburg-Landau (GL) length scales in the underdoped regime. We find that Tc has a sublinear dependence on 1/λ 2 ab , where λ ab is the in-plane magnetic penetration depth in the extrapolated limits T → 0 and H → 0. The power coefficient of the sublinear dependen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 55 publications
8
48
2
Order By: Relevance
“…5 are in qualitative agreement with a simplified quasiclassical "doppler-shift" calculation that has been reported previously 12 . The current results confirm the validity of the previous approximate calculations.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…5 are in qualitative agreement with a simplified quasiclassical "doppler-shift" calculation that has been reported previously 12 . The current results confirm the validity of the previous approximate calculations.…”
Section: Resultssupporting
confidence: 90%
“…Experimental measurements of the core size 12 , plotted in Fig. 5(c), show a similar variation at low field.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…For example, it has been found [16,17] that the vortex cores in YBa 2 Cu 3 O 7−δ , as measured by µSR experiments, are much larger at small magnetic fields B than expected from the measured upper critical field, and that the cores contract rapidly with increasing B below a crossover field B * . This anomalous behaviour has been explained by the presence of CuO chains [18,19], and it can be shown that B * ∼ E 2 s . It has also been suggested that a similar small energy scale seen in tunneling experiments [20,21,22] can be attributed to the chains.…”
Section: Introductionmentioning
confidence: 99%
“…However, this refined method is labor-consuming (e.g., the study in Ref. 7 was performed during several years). Moreover, the SR method is used to measure the magnetic field distribution in superconductors in the vortex state.…”
Section: Introductionmentioning
confidence: 99%